DETERMINANTS AND CONSEQUENCES OF WORK-LIFE BALANCE - Rosnani, Titik; Daud, Ilzar; Theresa, Revilia; Kalis, Maria Christiana Iman; Fahruna, Yulyanti (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
The work-life balance has become an important issue in the fast-paced and demanding work environment today. This study aims to analyze the determinants and consequences of work-life balance by examining the influence of working hours and job burnout on employee well-being, with the work-life balance as a mediating variable. It involved 100 active employees from the Local Government-Owned Water Utility of Pontianak City, chosen through a purposive sampling method. The data was collected using a questionnaire and analyzed using Structural Equation Modeling "“ Partial Least Square (SEM - PLS). The results reveal that the job burnout has a significant effect on both the work-life balance and employee well-being. However, the working hours does not have a significant effect on both the work-life balance and employee well-being. Additionally, the work-life balance has a significant effect on the employee well-being. Furthermore, this study confirms that the work-life balance is able to mediate the effect of job burnout on the employee well-being, but it is not able to mediate the effect of working hours on the employee well-being. These results provide managers and HR practitioners with insights into how to improve the employee well-being through effective working hours plans, job burnout reduction, and work-life balance programs.JEL:   I31, I39.